P243 Relative efficacy and safety of inhaled glycopyrronium+formoterol fumarate dihydrate versus other LAMA+LABA fixed-dose combinations in COPD: a systematic review and bayesian network meta-analysis. (December 2018) - Siddiqui, MK; Singh, I; Jenkins, M; Darken, P; Guranlioglu, D
Abstract : Introduction and objectives: Fixed-dose combination (FDC) therapies of long-acting muscarinic antagonists and long-acting β2 -agonists (LAMA+LABA) are indicated as maintenance treatment in chronic obstructive pulmonary disease (COPD). This Bayesian network meta-analysis (NMA) was performed to estimate the relative efficacy and safety of FDC glycopyrronium +formoterol fumarate dihydrate (GFF) 7.2/5.0 mcg two inhalations twice daily (b.i.d) compared to other LAMA+LABA FDCs in adult patients with moderate-to-very severe COPD in the absence of head-to-head studies. Methods: A systematic literature review (from database inception to January 2018) identified articles using biomedical databases (MEDLINE ®, Embase ® and Cochrane Central Register of Controlled Trials databases), conference proceedings and registry websites. Randomised controlled trials (RCTs) of ≥10 week duration, assessing LAMA+LABA combinations (≥1 treatment arm as LAMA+LABA FDC or open combination) in COPD patients aged ≥40 years were included. Outcomes of interest were: lung function (trough and peak forced expiratory volume in 1 s [FEV1 ]), symptoms (transition dyspnoea index [TDI] focal score and% of responders [>1 unit improvement]) at week 24, rescue medication over 24 weeks, health-related quality of life (HRQoL; St. George's Respiratory Questionnaire [SGRQ] total score and% responders [4-unit improvement]) at week 24, rate of any exacerbations and safety parameters. Results: Following screening, 25 studies from 166 citations (23 publications and 2 clinical study reports) were eligible for inclusion in the NMA. In general, efficacy of GFF was comparable, and not significantly different versus other LAMA+LABA FDCs for trough FEV1, peak FEV1, TDI focal score, TDI responders, SGRQ total score and SGRQ responders at week 24, rescue medication use over 24 weeks and rate of any exacerbations, wherever evidence was available for indirect comparison (table 1). The only statistically significant difference observed was a slight improvement in peak FEV1 for GFF in comparison to umeclidinium/vilanterol, with the mean difference in change from baseline of 34.74 mL (95% credible interval: 1.15, 69.65). The combinations were also comparable in terms of frequency of adverse events and all-cause withdrawals. Conclusions: This NMA demonstrates that GFF has comparable efficacy to other LABA+LAMA FDCs in terms of improving lung function, symptom control, HRQoL and reducing exacerbation rates, and has a comparable safety profile. *No restriction on timepoint, all studies 10 weeks or longer were included in the analysis.**Rescue medication use over 24 weeks of treatment. # Not statistically significant. † Statistically significant.For change from baseline in SGRQ score and rescue medication use, negative values favour GFF. For change from baseline in TDI, values>0 favour GFF. For SGRQ responders, values of >1 favour GFF. For TDI responders, values of >1 favour GFF.b.i.d., twice daily; CrI, credible interval; FDCs, fixed-dose combinations; FEV1, forced expiratory volume in 1 s; LABA, long-acting β2 -agonist; LAMA, long-acting muscarinic-antagonist; MD, mean difference; o.d, once daily; OR, odds ratio; RR, rate ratio; SGRQ, St. George's respiratory questionnaire; TDI, transition dyspnoea index.Treatments: GFF, glycopyrronium/formoterol fumarate dihydrate 7.2 mcg/5.0 mcg b.i.d (equivalent to glycopyrrolate/formoterol fumarate 9 mcg/4.8 mcg, b.i.d).ACL/FOR, aclidinium/formoterol fumarate dihydrate 340 mcg/12 mcg b.i.d.TIO/OLO, tiotropium/olodaterol 2.5 mcg/2.5 mcg o.d.UME/VIL, umeclidinium/vilanterol 55 mcg/22 mcg o.d.GLY/IND, glycopyrronium/indacaterol 43 mcg/85 mcg o.d.